2015
DOI: 10.1097/mnh.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Current MRI techniques for the assessment of renal disease

Abstract: Purpose of review Over the past decade a variety of magnetic resonance imaging (MRI) methods have been developed and applied to many kidney diseases. These MRI techniques show great promise, enabling the noninvasive assessment of renal structure, function, and injury in individual subjects. This review will highlight current applications of functional MRI techniques for the assessment of renal disease and discuss future directions. Recent findings Many pathological (functional and structural) changes or fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 70 publications
2
39
0
1
Order By: Relevance
“…An important imaging parameter in DWI is the apparent diffusion coefficient (ADC), which quantifies the magnitude of the diffusion process of water molecules within the tissue . DWI has been shown to detect the changes in diffusion processes caused by kidney pathologies . A previous study showed that ADC values decrease with CKD depending on the extent of the injury.…”
Section: Introductionmentioning
confidence: 99%
“…An important imaging parameter in DWI is the apparent diffusion coefficient (ADC), which quantifies the magnitude of the diffusion process of water molecules within the tissue . DWI has been shown to detect the changes in diffusion processes caused by kidney pathologies . A previous study showed that ADC values decrease with CKD depending on the extent of the injury.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive nephropathy constitutes a major cause of pediatric renal progressive disease. To date, the follow‐up of patients has been difficult as the progression of the disease is poorly understood and there is a lack of non‐invasive biomarkers . The indication for surgery generally depends on imaging criteria, requiring a few months of follow‐up of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Renal biopsy is the standard method for assessing renal fibrosis. Several MRI techniques, [9][10][11] including blood oxygenation-level-dependent (BOLD) imaging and diffusion weighted imaging (DWI), have also been used to assess renal fibrosis. 6 Ultrasound has shown some promising results in measuring renal cortical stiffness.…”
mentioning
confidence: 99%